Pengaruh Perilaku Pengunjung terhadap Loyalitas Konsumen pada Desa Pulau Pahawang Kabupaten Pesawaran - Kusnadi, Danang; Sandra, Mela (Universitas Mitra Indonesia, 2022)
Consumer behavior is crucial in the decision making process to buy, spend or take something. Stagesbegins with problem recognition, search for information, evaluation of alternatives, purchase decision. Post-purchase last is dependent on the level of satisfaction derived from the product or service. This is in line with the assessment of visitor behavior and visitor loyalty level to make a visit to a tourist attraction. Based on the above it can be the identification of the problem, there are some weaknesses in the system thatal ready applies, namely: 1). Are Variable Perception, Learning and Attitude affects customer loyalty? 2). Among the existing variables, which variables that have a dominant influence on consumer loyalty ?Based on data analysis that has been done can be concluded as follows: 1). The results of multiple regression test showed that a variable perception, learning and Attitude has a significant influence on customer loyalty variables. 2) The results of the t test showed that the partial of perception, learning and Attitude significant effect on loyalty. 3) Simultaneously, it can be said that perception, learning and Attitude has a significant influence on customer loyalty. 4) From the ANOVA test or F test F count was obtained with a significant level of 0.000 1102.095 because the probability is much smaller than 0.05, then the perception (X1), Learning (X2) and Attitude (X3) together (simultaneous) effect on loyalty (Y). 5) The most influential variable is learning.